Isolation and identification of pathogenic bacteria in the Batanghari River, Jambi - Hasna Ul Maritsa; Raudatul Jannah (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
Research on the isolation and identification of pathogenic bacteria in the Batanghari River, Jambi, was conducted from November to February 2023. The purpose of this research was to identify pathogenic bacteria in the Batanghari River, Jambi. The research method involved purposive sampling in the field and bacterial identification tests in the laboratory. Samples from the field were diluted, inoculated, and incubated on Nutrient Agar (NA) media for 24 hours. Macroscopic observations included the shape, color, elevation, texture, and surface of the bacterial isolates. Microscopic observations included the bacterial cell shape and characteristics in Gram staining. The research results showed the presence of pathogenic bacteria from the Vibrio cholera group